What's new in evaluation research? A note on the Pawson and Tilley article - Bennett, Trevor (The British journal of criminology, 1996)
This paper examines the criticisms of quasi-experimental design included in a recent article by Pawson and Tilley 1994. The note argues that the criticisms are poorly developed and unconvincing and concludes that the article provides us with little that is new and nothing that is useful in developing research methods in criminology